2001
DOI: 10.1111/j.1600-0463.2001.tb05793.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic potential of xenobiotic growth promoters and their metabolites

Abstract: potential of xenobiotic growth promoters and their metabolites. APMIS 2001;109:89-95.This paper reviews data reported in the literature as well as recent and unpublished studies from our laboratory on the metabolism and genotoxicity of the xenobiotic growth promoters 17b-trenbolone, melengestrol acetate and zeranol. In our metabolic study, the oxidative in vitro metabolites generated by hepatic microsomes from rats, bovine and humans were analyzed by HPLC and GC/MS. 17b-Trenbolone gave rise to at least 13 mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 11 publications
0
10
0
8
Order By: Relevance
“…However, our results showed that the strong estrogenic activity, usually attributed to ZEN, cannot explain all these adverse effects observed on nonspecific target cells for ZEN estrogenic activity (Vero cells). As described by Bettershill and Fielder [44] and Metzler and Pfeiffer [45], these toxic effects can be attributed to ZEN or to its metabolites. These can also be attributed to reactive oxygen species generated by ZEN [13,46,47].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, our results showed that the strong estrogenic activity, usually attributed to ZEN, cannot explain all these adverse effects observed on nonspecific target cells for ZEN estrogenic activity (Vero cells). As described by Bettershill and Fielder [44] and Metzler and Pfeiffer [45], these toxic effects can be attributed to ZEN or to its metabolites. These can also be attributed to reactive oxygen species generated by ZEN [13,46,47].…”
Section: Discussionmentioning
confidence: 91%
“…As described by Bettershill and Fielder [44] and Metzler and Pfeiffer [45], these toxic effects can be attributed to ZEN or to its metabolites. These can also be attributed to reactive oxygen species generated by ZEN [13,46,47].…”
Section: Discussionmentioning
confidence: 95%
“…They were very weakly positive in a micronucleus test, at high (potentially cytotoxic) concentrations. Trenbolone also produced a low level of DNA adducts measured by 32P-post-labelling (Metzler and Pfeiffer, 2001). As indicated above, micronuclei can arise via a non-genotoxic mechanism, particularly at concentrations that may have caused some toxicity.…”
Section: Dr Boobismentioning
confidence: 99%
“…The Scientific Committee on Veterinary Measures Relating to Public Health (1999) concluded that current evidence is insufficient to complete a quantitative assessment of risk. A more recent report by Metzler & Pfeiffer (2001) reviewed current information on the genotoxic potential of TB-17β-OH and metabolites using a range of in vitro tests. Negative results were obtained for the hypoxanthine phosphoribosyl transferase system in V79 cells and at the LACl gene locus in Escherichia coli.…”
Section: Genotoxicity Carcinogenicity and Effects On Growth Developmentioning
confidence: 99%
“…This dose is typical of that given to cattle. More recently, evidence has been reviewed for the genotoxicity of Z and metabolites in a range of systems including induction of hypoxanthine phosHormones in meat production 307 phoribosyl transferase and LAC1 mutations in cultured V79 cells and E. coli respectively, induction of micronuclei in V79 cells and adduct formation in cultured primary rat hepatocytes (Metzler & Pfeiffer, 2001). A 'marginally positive' response for Z and its major metabolites α-zearalanone and taleranol in the micronucleus induction test was reported at concentrations approaching the cytotoxic.…”
Section: Genotoxicity Carcinogenicity and Effects On Growth Developmentioning
confidence: 99%